Conceptos basicos para el mejoramiento del frijol por hibridacion - Singh, Shree P. (United Nations Development Programme, 1985)
The basic concepts of the genetic improvement of beans through hybridization are described. In general, the breeding process involves the following phases: (1) development of exptl. lines, (2) evaluation of exptl. lines and identification of new cv., and (3) commercialization of new cv. The main aspects that should be considered in the development of exptl. lines as well as the most common breeding methods used in beans (modified pedigree, mass- pedigree, and backcrossing) are described. The evaluation of exptl. lines and the identification of new cv. are carried out in 3 or more steps: adaptation nurseries, preliminary yield trials, and regional yield trials. For the commercialization of new cv. the newly identified materials are registered, multiplied, and distributed. (CIAT)